2009
DOI: 10.1111/j.1439-0396.2008.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual response of growing pigs to lysine intake

Abstract: Nitrogen (N) balance experiment was carried out to study the individual and group response of growing pigs to lysine (Lys) intake. A series of 15 purified diets limiting in Lys were fed sequentially to nine pigs (initial body weight, 39 kg) during a 15-day experiment. Lysine concentration ranged from 50% to 140% of its assumed requirement. N retention in individual pigs was related to Lys intake using linear-plateau (LP) and quadratic-plateau (QP) models. No difference in the closeness of fit between the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…The 5.2% coefficient of variation is consistent with the findings of published studies about the response of growing pigs to amino acid intake (Heger et al, 2007;Heger et al, 2008;Heger et al, 2009). This indicates that the maximum protein deposition rate also varies considerably among individuals, even when animals present homogenous characteristics (genetic strain, age, and sex) and are evaluated under the same environmental and health-challenged conditions.…”
Section: Discussionsupporting
confidence: 86%
“…The 5.2% coefficient of variation is consistent with the findings of published studies about the response of growing pigs to amino acid intake (Heger et al, 2007;Heger et al, 2008;Heger et al, 2009). This indicates that the maximum protein deposition rate also varies considerably among individuals, even when animals present homogenous characteristics (genetic strain, age, and sex) and are evaluated under the same environmental and health-challenged conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Pour l'obtention de valeurs individuelles de besoin, Heger et al (2007Heger et al ( , 2008Heger et al ( , 2009 ont utilisé une méthode de bilans azotés consécutifs de 24 heures chacun, en réponse à de petites augmentations de l'acide aminé limitant dans le régime. Après 4 jours d'adaptation au régime le plus carencé, chaque animal étudié reçoit consécutivement sur 15 jours, 15 niveaux d'apport de l'acide aminé étudié augmentant graduellement de 50 à 140% du besoin estimé.…”
Section: / Détermination Expérimentale De La Variabilité Des Besoins unclassified
“…L'ajustement d'un modèle quadratique plateau ou linéaire-plateau à la réponse de chaque individu permet d'obtenir le besoin en l'acide aminé étudié pour chaque porc et sa variabilité entre les animaux étudiés. Ces auteurs évaluent ainsi expérimentalement sur neuf femelles croisées Large White x (Large White x Landrace) le Coefficient de Variation (CV) du besoin en acide aminé (en valeur digestible standardisée) à 3% à 45 kg de Poids Vif (PV) pour la thréonine (Heger et al 2007), à 11% à 50 kg de PV pour la méthionine (Heger et al 2008) et à 10% à 47 kg de PV pour la lysine (Heger et al 2009).…”
Section: / Détermination Expérimentale De La Variabilité Des Besoins unclassified
“…Other studies have demonstrated the lack of difference between pigs fed below the requirement with l-Lys·HCl or soybean meal (SBM)-bound Lys for PD (Susenbeth et al 1994;Liebert, 1995;Colina et al, 2013). Moreover, Heger et al (2009) indicated that pigs with a greater PD rate do not utilize Lys more efficiently compared to pigs with less PD.…”
mentioning
confidence: 99%